2006
DOI: 10.1111/j.1439-0442.2006.00819.x
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydiales in Guinea‐pigs and Their Zoonotic Potential

Abstract: The aim was to detect and characterize chlamydial infections in guinea-pigs (GP) with ocular disease, study their pathogenicity and zoonotic potential and to test for the presence of Acanthamoebae spp. in GP eyes and to investigate whether they could act as vectors for Chlamydia-like organisms. Overall 126 GP, of which 77 were symptomatic, were screened by clinical examination, cytology, gross pathology, histology, immunohistochemistry, polymerase chain reaction (PCR) and bacteriology. A new Chlamydiaceae-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
6
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 35 publications
2
60
6
6
Order By: Relevance
“…The Chlamydiaceae species are known to be very host specific, and in our study we identified Chlamydophila species only in their expected hosts. However, other studies have shown that one species may be isolated from various hosts (4,6,9,13,16,17). Host specificity may be viewed in terms of primary or principal hosts and occasional hosts (20), where the infection usually spreads from the primary host to occasional hosts living in close proximity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Chlamydiaceae species are known to be very host specific, and in our study we identified Chlamydophila species only in their expected hosts. However, other studies have shown that one species may be isolated from various hosts (4,6,9,13,16,17). Host specificity may be viewed in terms of primary or principal hosts and occasional hosts (20), where the infection usually spreads from the primary host to occasional hosts living in close proximity.…”
Section: Discussionmentioning
confidence: 99%
“…This is illustrated in Cp. caviae isolated from the primary host (a guinea pig) but also detected in the animal's owner, as well as in a cat and a rabbit in the household (16). Usually, primary hosts are sampled because they show typical clinical signs, but the larger host diversity applicable for Chlamydophila sp.…”
Section: Discussionmentioning
confidence: 99%
“…Two liters of water samples were fi ltrated through 0.22-μm pore-sized fi lters that were injected onto amebal microplates as previously described (6) and incubated at 32°C. We screened amebal microplates by examination under inverted microscope and by ZiehlNielsen, Gram, and Gimenez staining.…”
Section: Emerging Mycobacteria Spp In Cooling Towersmentioning
confidence: 99%
“…Of interest, a recent study of 482 healthy Swiss men found 3 who were seropositive for Parachlamydia sp., and all 3 came from the same rural area near Lausanne (within <20-km radius) (9). Moreover, the patient owns 2 guinea pigs, potential vectors of the bacterium (6). Other modes of transmission are possible, e.g., contaminated water (free-living amebae may serve as hosts for Parachlamydia spp.…”
mentioning
confidence: 99%
“…Both are considered to be important emerging pathogens in animals with zoonotic potential (Greub and Raoult 2002) and they might be regarded as new abortigenic agents in Swiss and Scottish cows (e.g., Ruhl et al 2009;Deuchande et al 2010). Moreover, P. acanthamoebae has been associated with ocular lesions in naturally infected guinea pigs (Cavia porcellus; Lutz-Wohlgroth et al 2006) and cats (Felis catus; Richter et al 2010) and was recently shown to produce pneumonia in an experimental murine lung infection model (Casson et al 2008b). Parachlamydia and Waddlia DNA have been detected in several ruminant wildlife species in Switzerland (Regenscheit et al 2012) and even in environmental samples such as drinking and well water for cattle (Bos primigenius) (Wheelhouse et al 2011;Codony et al 2012).…”
Section: Introductionmentioning
confidence: 99%